Social Security and Taxation of Labour Subject to Subsidiarity and Freedom of Movement - Wolfram F. Richter (Institute for the Study of Labor (IZA), 2002)
In Europe, the competence for social security and the right to levy income tax lie with the country of employment in cross-border matters. This has two disadvantages. First, the Employment Principle distorts active persons' choice of place of work. Second, the employment-based regulation of state competencies cannot be applied to non-active persons. The Treaty of Maastricht, however, confers the right of free movement to all citizens of the Union. Against this background, this paper pleads for a reform in European policy coordination. The Employment Principle should be replaced with the Principle of Delayed Integration where cross-border matters are concerned.
Keywords: J61; H70; H21; 330; Social security and taxation of mobile labour; Employment Principle; Delayed Integration; Origin Principle; free movement; Internationale Arbeitsmobilität; Sozialversicherungsbeitrag; Einkommensteuer; EU-Steuerrecht; Freizügigkeit; Ursprungslandprinzip; EU-Staaten